Organizational ethics and stakeholder well-being in the business environment - Valentine, Sean (Ethics in practice (Greenwich, Conn.), 2014)
Organizational ethics involves the institutionalized principles, guidelines, and norms that influence how a company and its employees function in an ethical manner. Ultimately, these processes collectively influence a firm's 1) overall sense ofbusiness ethics, 2) management of employees, and 3) interactions with partners outside of the immediate work environment. Researcher and practitioners are interested in organizational ethics because the different approaches used to develop such a context generate many other positive business outcomes.While the connection between organizational ethics and employee/stakeholder well-being has been explored, moving forward with a number of new investigations should push the literature forward. This book seeks to explore these important topics and present a more comprehensive overview of organizational ethics and stakeholder well-being in the business environment. Such inquiry is important because the linkages between business ethics and stakeholders, if wellmanaged, have the capacity to benefit both companies and employees. In addition, the content of this book should serve to guide future investigations within this area of business ethics.